High-Dose Micafungin in Neonates and Young Infants with Invasive Candidiasis: Results of a Phase 2 Study - Auriti, Cinzia (Antimicrob Agents Chemother, 2021)
Limited data are available on the most appropriate dosing, efficacy, and safety of micafungin in neonates and young infants with invasive candidiasis (IC). This study evaluated plasma levels, efficacy, and safety of micafungin at a dose of 8 mg/kg daily for a mean of 13.3 days (±5.2 days) in 35 neonates and young infants with IC. Micafungin plasma concentrations were 5.70 mg/liter preadministration and 17.23, 15.59, and 10.27 mg/liter after 1, 2, and 8 h, respectively. The resolution of the infection was achieved in 86.7% of patients treated for ≥14 days. In 20.0% of patients, we observed a transient hypertransaminasemia. Micafungin at a dose of 8 mg/kg daily is effective and well tolerated in neonates and young infants with IC. (This study has been registered at ClinicalTrials.gov under identifier NCT03421002 and in the EU Clinical Trials Register under number 2014-003087-20.)